Upaya Meningkatkan Kepuasan Wisatawan Melalui Fasilitas di Kampung Buricak Burinong - Della Maghfira Napu; Wildan Nurhidayat; Ervina Damayanti; Astrie Noviyanti; Resi Nur Rahmawati (Universitas Muhammadiyah Palembang, 2025)
Tourist facilities are one of the crucial elements in supporting tourism activities in tourist destinations. Adequate facilities will provide comfort for tourists when visiting tourist destinations. This is in line with the increase in tourist visits to Sumedang Regency, but there has been a decrease in visits to Buricak Burinong Village. This is allegedly because the facilities available in Buricak Burinong Village do not meet the desires and needs of visitors. The aim of this research is to find the effect of facilities on the level of visitor satisfaction in Buricak Burinong Village. This quantitative descriptive study was conducted to determine the influence of facilities and visitor satisfaction in Buricak Burinong Village. Data was collected through a survey of 100 visitors using a questionnaire. Respondents were selected using the Convenience Sampling method. Data were analyzed using F Test, T Test, and path analysis. Research findings reveal a significant influence of facilities on visitor satisfaction. It is hoped that the quality of the existing facilities in Buricak Burinong Village can be improved so that they can provide maximum satisfaction and increase tourist visits according to the predetermined targets.